The 2002–2005 Changbaishan Volcanic Unrest Triggered by the 2002 M 7.2 Wangqing Deep Focus Earthquake - Liu, Guoming; Li, Chenyu; Peng, Zhigang; Liu, Yinan; Zhang, Yu; Liu, Dongyang; Zhang, Maoliang; Pan, Bo (Frontiers in Earth Science, 2021)
Using a template matching technique, we perform systematic detection of microseismic events through continuous waveforms recorded by station CBS, which is deployed near the Changbaishan volcano in Northeast China. The detected earthquakes can be further categorized into three different types: volcano-tectonic (VT) events, long-period (LP) events and harmonic-spectra (HS) events. We detect 3763 VT events between July 2002 and July 2007. The intense VT earthquake swarm during the period from July 2002 to July 2005, along with recurring LPs and HSs and other geodetic/geochemical evidence, suggest the occurrence of a volcanic unrest in this time window. The significantly increased seismicity after the 2002/06/28 Mw 7.2 Wangqing deep-focus earthquake suggests that it might have triggered the 3-year earthquake swarm with a delayed response of seven days. During the period of volcanic unrest, 20 LP events with dominant frequencies of 2–3 Hz and 125 HS events with harmonic spectra are confirmed. The small magnitudes of the VT events and the limited numbers of LP and HS events suggest that the Wangqing deep-focus earthquake likely triggered bubble excitation in the mid-crust magma system, resulting in overpressure and a small magma injection into the shallow magma chamber at a depth of ~5 km.